Silencing of a putative immunophilin gene in the cattle tick Rhipicephalus (Boophilus) microplus increases the infection rate of Babesia bovis in larval progeny - Knowles Donald P; Guerrero Felix D; Ueti Massaro W; Bastos Reginaldo G; Scoles Glen A (Parasites & Vectors, 2009)
Abstract Background The cattle tick Rhipicephalus (Boophilus) microplus is involved in the transmission of the protozoan Babesia bovis, the etiological agent of bovine babesiosis. Interactions between ticks and protozoa are poorly understood and the investigation of tick genes that affect tick fitness and protozoan infection can set the stage for dissecting the molecular interactions between the two species. Results In this study, RNA interference was used to silence R. microplus genes that had been previously shown to be up-regulated in response to B. bovis infection. The silencing of a putative immunophilin gene (Imnp) in female ticks fed on a calf acutely infected with B. bovis decreased the hatching rate and survival of larval progeny. Interestingly, Imnp was up-regulated significantly in ovaries of R. microplus in response to B. bovis infection and its silencing in female ticks significantly increased the infection rate of the protozoan in larval progeny. The results also showed that the silencing of a putative Kunitz-type serine protease inhibitor (Spi) gene and a putative lipocalin (Lpc) gene decreased the fitness of R. microplus females, but had no significant effect on the infection rate of B. bovis in larval progeny. Conclusion The silencing of the Imnp, Spi or Lpc genes decreased the fitness of R. microplus females fed on a calf during acute B. bovis infection. The Imnp gene data suggest that this putative immunophilin gene is involved in the defense system of R. microplus against B. bovis and may play a role in controlling the protozoan infection in tick ovaries and larval progeny.